2020
DOI: 10.3758/s13415-020-00783-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline-dependent effect of dopamine’s precursor L-tyrosine on working memory gating but not updating

Abstract: Adaptive goal-directed behavior requires a dynamic balance between maintenance and updating within working memory (WM). This balance is controlled by an input-gating mechanism implemented by dopamine in the basal ganglia. Given that dopaminergic manipulations can modulate performance on WM-related tasks, it is important to gain mechanistic insight into whether such manipulations differentially affect updating (i.e., encoding and removal) and the closely-related gate opening/closing processes that respectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 64 publications
5
15
1
Order By: Relevance
“…In this study, we performed the first detailed model-based analysis of behavioral costs in the reference-back task, which are assumed to reflect a set of cognitive control processes that support WM. Our data replicated the set of behavioral effects found in previous reference-back studies [11,12,14,[21][22][23][24][25], including the asymmetrical costs of opening and closing the gate to WM [7,11,12,14,21]. The DDM provided close fits to empirical choice-RT distributions for each design cell of the reference-back, and model selection indicated that, for most subjects, drift rate and non-decision time each played an important role in explaining the observed differences in accuracy and RT.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, we performed the first detailed model-based analysis of behavioral costs in the reference-back task, which are assumed to reflect a set of cognitive control processes that support WM. Our data replicated the set of behavioral effects found in previous reference-back studies [11,12,14,[21][22][23][24][25], including the asymmetrical costs of opening and closing the gate to WM [7,11,12,14,21]. The DDM provided close fits to empirical choice-RT distributions for each design cell of the reference-back, and model selection indicated that, for most subjects, drift rate and non-decision time each played an important role in explaining the observed differences in accuracy and RT.…”
Section: Discussionsupporting
confidence: 89%
“…To summarize, the canonical reference-back cost measures were all associated with slower RT and, for gate opening and substitution, lower accuracy. In addition, the larger RT cost for gate closing versus gate opening replicates the asymmetric gating costs found in previous works [7,11,12,14,21]. These effects are illustrated in Figure 4.…”
Section: Conventional Analysessupporting
confidence: 85%
See 3 more Smart Citations